Codesign Methodology based FPGA and Embedded Linux for Motor Control - Ibtihel Jaziri; Lotfi Charaabi; Khaled Jelassi (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Recently, the complexity of the embedded electrical systems is increasing due to the growing of industrial necessities. To handle with this complexity, the use of reconfigurable hardware/software codesign methodology using digital platforms becomes necessary. Reconfigurable methodology can be seen as an essential feature in motor control systems as it offers many advantages such as increased flexibility, low energy consumption. In these kind of systems, both hardware and software designs can be reconfigurated depending upon the designer requirements. This paper presents hardware/software codesign methodology with flexible hardware devices and configurable graphical user interface: the hardware architecture is based on field-programmable gate array and the software architecture is based on embedded Linux operating system running on Beaglebone. The user interface is designed as a graphical user interface developed on an emebdded server; this enables the user to access to the system rapidly, parameterize and observe the behavior of the controller.